Intramuscular Corticosteroids for Acute Upper Respiratory Infections Affects Healthcare Utilization. (October 2020) - Parsel, Sean M; Mohammed, Alaa E; Fort, Daniel; Barton, Blair M; McCoul, Edward D
Objective: To examine the use of intramuscular corticosteroid (IMCS) injections for treatment of acute upper respiratory infections (URI) and the influence on healthcare utilization. Methods: This retrospective cohort study used patient encounter data from a large multicenter regional health care system between 2013 and 2017. Adult patients diagnosed with acute URI (acute pharyngitis, acute sinusitis, acute otitis media, and URI not otherwise specified) during ambulatory encounters were included. Follow-up encounters for a diagnosis of acute URI within 60 days were identified and patient characteristics, encounter details, and procedure codes were retrieved. Frequency data was used to calculate IMCS injection administration prevalence, utilization trends, and associations with covariates. Follow-up data for return encounters within 60 days for the same diagnosis was examined. Results: Of the 153 848 initial encounters, 34 600 (22.5%) patients received IMCS injection for acute URI. Injection rates varied from 0.85% to 49.1% depending on specialty and practitioner type. Internal medicine, family medicine, urgent care, and otorhinolaryngology clinics most commonly administered IMCS. 3788 patients returned for a second encounter of which 751 (19.8%) received an injection. IMCS injection during the first encounter was associated with increased odds of repeat visit within 60 days (OR: 1.74; 95% CI: 1.61–1.88). Conclusion: IMCS use in the treatment of acute URI is highly prevalent despite lack of evidence for impact and safety. Prevalence is variable across multiple medical and surgical specialties including otorhinolaryngology. Administration of IMCS injection may contribute to the likelihood of a subsequent healthcare visit for the same indication.